Myocardial left ventricular dysfunction in patients with systemic lupus erythematosus: new insights from tissue doppler and strain imaging - Buß, Sebastian Johannes; Wolf, David Gregor; Korosoglou, Grigorios; Max, Regina; Weiss, Celine; Fischer, Christian; Schellberg, Dieter; Zugck, Christian; Kücherer, Helmut; Lorenz, Hanns-Martin; Katus, Hugo; Hardt, Stefan; et al. (The journal of rheumatology, 2010)
Objective. Systemic lupus erythematosus (SLE) is associated with high cardiovascular morbidity and mortality. Cardiovascular involvement is frequently underestimated by routine imaging techniques. Our aim was to determine if new echocardiographic imaging modalities like tissue Doppler (TDI), strain rate (SRR), and strain (SRI) imaging detect abnormalities in left ventricular (LV) function in asymptomatic patients with SLE. - Methods. Sixty-seven young patients with SLE (mean age 42 ± 10 yrs) without typical symptoms or signs of heart failure or angina, and a matched healthy control group (n = 40), underwent standard transthoracic echocardiography, TDI, SRR, and SRI imaging of the LV as well as assessment of disease characteristics. - Results. Despite findings within the normal range on routine standard 2-dimensional echocardiography, SLE was associated with significantly impaired systolic and diastolic myocardial velocities of the LV measured by TDI [mean global TDI: systolic (s): 2.9 ± 0.9 vs 3.9 ± 0.7 cm/s, p < 0.05; early (e): 4.3 ± 1.5 vs 6.3 ± 1.3 cm/s, p < 0.05; late (a): 2.9 ± 0.8 vs 3.4 ± 0.8 cm/s, p < 0.05; values ± SD); SRR (s: −0.8 ± 0.1 vs −1.1 ± 0.1 s−1; e: 1.1 ± 0.2 vs 1.6 ± 0.3 s−1; a: 0.7 ± 0.1 vs 1.0 ± 0.2 s−1; all p < 0.05); and SR (−15.11 ± 2.2% vs −19.7 ± 1.9%; p < 0.05) compared to the control group. Further, elevated disease activity, measured with the ECLAM and the SLEDAI score, resulted in significantly lower values for LV longitudinal function measured by SRR and SR, but not by TDI. - Conclusion. SLE is associated with a significant impairment of systolic and diastolic LV longitudinal function in patients without cardiac symptoms. New imaging modalities provide earlier insight into cardiovascular involvement in SLE and seem to be superior to standard echocardiography to detect subclinical myocardial disease.
Erstmals am 29. Dezember 2009 online veröffentlicht
Gesehen am 22.03.2023